(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
on the analysis of this painting that the German philosopher Martin Heidegger makes in his book The Origin of the Work of Art (1937), from which we create a rich debate, primarily concerned with the origin and ultimate meaning of Van Gogh´s work. This paper seeks to combine phenomenologically, the wing of thought of Martin Heidegger, the set of pictures he painted on the Dutch painter “shoe model” under the “theme of walking”, understood as a “wandering” in Van Gogh dramatic turns in search of belonging, but especially for subsistence conditions, both physical and spiritual. So the shoe becomes an emblem, the vehicle with which to travel in the rugged geography of his wandering.